Investigation Of Different Rules Size FLSC Performance Applied To Induction Motor Drive - Talib, Md Hairul Nizam; Ibrahim, Zulkifilie; Rasin, Zulhani; Mat Lazi, Jurifa; Azri, Maaspaliza (Penerbit Universiti, UTeM, 2017)
Fuzzy Logic Controller (FLC) has been widely used in speed controller due to its superior performance results. It is suitable when the system is difficult to model mathematically due to its nonlinearity and complexity. There are three common number of rules design which are commonly used in FLSC known as 49, 25 and 9 rules. However, the majority of the previous research report mainly focused on the dedicated rules size design either 49, 25 or 9 rules for the optimum performance. There is lack of performance comparison between 49, 25 and 9 rules size. Thus, it is difficult to understand how the rules size affects the motor performance. This research tries to fill up the gap by comparing the controller performance using the same platform. The fuzzy logic speed controllers (FLSC) with a different type of rules base are applied to the induction motor drive system. The FLSC with 49, 25 and 9 rules are investigated through MATLAB/SIMULINK and performance comparisons are made covering a wide speed range operations and load disturbance. The simulation results are evaluated based on the rise time (